Adaptation of the Tool to Estimate Patient Costs Questionnaire into Indonesian Context for Tuberculosis-affected Households - Ahmad Fuady; Tanja A Houweling; Muchtaruddin Mansyur; Jan H Richardus (Acta Medica Indonesiana)
Background: Indonesia is the second-highest country for tuberculosis (TB) incidence worldwide. Hence, it urgently requires improvements and innovations beyond the strategies that are currently being implemented throughout the country. One fundamental step in monitoring its progress is by preparing a validated tool to measure total patient costs and catastrophic total costs. The World Health Organization (WHO) recommends using a version of the generic questionnaire that has been adapted to the local cultural context in order to interpret findings correctly. This study is aimed to adapt the Tool to Estimate Patient Costs questionnaire into the Indonesian context, which measures total costs and catastrophic total costs for tuberculosis-affected households. Methods: the tool was adapted using best-practice guidelines. On the basis of a pre-test performed in a previous study (referred to as Phase 1 Study), we refined the adaptation process by comparing it with the generic tool introduced by the WHO. We also held an expert committee review and performed pre-testing by interviewing 30 TB patients. After pre-testing, the tool was provided with complete explanation sheets for finalization. Results: seventy-two major changes were made during the adaptation process including changing the answer choices to match the Indonesian context, refining the flow of questions, deleting questions, changing some words and restoring original questions that had been changed in Phase 1 Study. Participants indicated that most questions were clear and easy to understand. To address recall difficulties by the participants, we made some adaptations to obtain data that might be missing, such as tracking data to medical records, developing a proxy of costs and guiding interviewers to ask for a specific value when participants were uncertain about the estimated market value of property they had sold. Conclusion: the adapted Tool to Estimate Patient Costs in Bahasa Indonesia is comprehensive and ready for use in future studies on TB-related catastrophic costs and is suitable for monitoring progress to achieve the target of the End TB Strategy.